PENGARUH PENYULUHAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENCEGAHAN DAN PENGENDALIAN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS PESANGGRAHAN KABUPATEN MOJOKERTO - Kadek Gede Dhiyo Bhargo Yasa; Nur Khamidah; Ayu Cahyani Noviana; Wike Herawaty; Rani Nur Rafli Amalia; Niken Triyulianita S; Lailatul Jannah; Aflacha Alivia Risalatul I; Ni Putu Santhi Cahya Dewi; Kadek Rio Risnanda; I Komang Adhi Arya Yudanta; Kristian Aribowo (Jurnal Riset Multidisiplin Edukasi, 2026)
Diabetes Mellitus Type 2 (T2DM) is a chronic metabolic disease and remains a major public health problem in Indonesia, particularly among the elderly population. Community-based preventive efforts through health education are essential to reduce the incidence and complications of T2DM. This community service activity aimed to improve knowledge, awareness, and preventive behavior regarding T2DM through health education among elderly residents in Windurejo Village, Mojokerto Regency. The target participants were elderly individuals who are at high risk for T2DM and its complications. The method used was participatory health education employing booklet media, interactive discussions, question-and-answer sessions, and evaluation through pre-test and post-test questionnaires. The material covered the definition, risk factors, signs and symptoms, management, prevention strategies, and diabetic foot exercise. The activity was conducted on February 27, 2026, with 30 participants. Evaluation results showed a significant increase in knowledge, indicated by the proportion of correct answers rising from 55% in the pre-test to 93% in the post-test. Several modifiable risk factors were identified, including high sugar intake, low physical activity, obesity, and family history of diabetes. In conclusion, health education effectively improved elderly knowledge and awareness regarding T2DM prevention and encouraged healthy lifestyle practices. Continuous community-based education programs are recommended to support sustainable diabetes control efforts.